Promising Research and Strategies in Wastewater Treatment, Sludge Management and Valorization - Pérez, Amanda Laca; Patiño, Yolanda (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Rapid urbanization and industrialization, in addition to the presence of new pollutants, make it necessary to search for new wastewater treatment technologies to achieve future water quality requirements. Additionally, waste reduction and the reuse of treated wastewater seem to be excellent options to realize the concept of a circular economy. This Reprint compiles the latest research on relevant wastewater treatment concerns, including the occurrence of emerging contaminants and their removal in wastewater treatment plants (WWTPs), novel technologies for wastewater and sludge treatment, sludge valorization, the transformation of agricultural residues into materials for wastewater treatment, biodegradation of recalcitrant compounds, etc.